Characteristics of trichloroethene (TCE) dechlorination in seawater over a granulated zero-valent iron. (February 2019) - Shih, Yu-Jen; Hsia, Kuo-Feng; Chen, Chiu-Wen; Chen, Chih-Feng; Dong, Cheng-Di
Abstract: The accumulation of halogenated organic contaminants in estuaries near harbor areas has been receiving increasing attention. This work demonstrates the reductive treatment of trichloroethene (TCE) within seawater and freshwater using a polymeric surfactant (polyvinyl alcohol- co -vinyl acetate-coitaconic acid) modified nanoscale zero-valent iron (GnZVI). Experimental parameters included the ratio of seawater to freshwater, reaction pH, dosage of GnZVI and initial TCE concentration. It was found that the rate of TCE reduction decreased with increasing weight ratio of seawater to freshwater ( k a = 0.075 min −1 in freshwater and 0.01 min −1 in seawater); however, the rate substantially improved by increasing the dosage of GnZVI. A consecutive reaction model of adsorption/desorption and reductive dechlorination was established to assess the chemical kinetics of TCE and the intermediates over the GnZVI. The experimental results suggested that both the amount of free sites on the reductant and reactivity of iron to TCE dominated the degradation efficiency. Desorption was a rate-limiting step for the intermediates that evolved (DCE, VC and ethene) in the bulk solution. Under conditions: GnZVI = 5 g/L, reaction pH around 8 and initial TCE = 10 mg/L, the removal efficiency attained 95%, while the decline in the removal rate of TCE from the seawater could be simply improved by increasing GnZVI dosage (10 g/L). As a role of electron donor for water and TCE, ZVI might passivate with contact time, leading to formation of the main crystalline phase magnetite (Fe3 O4 ) by the coprecipitation of oxidized iron (Fe(II)/Fe(III)) over the surfaces of ZVI particles. Highlights: A granulated zero-valent iron was prepared using the polymeric surfactant. TCE reduction by Fe 0 was assessed by kinetics of adsorption and chemical reaction. GnZVI maintained a high reductive effectiveness system in seawater. Characterization evidenced the granulation and passivation of iron. Rate of intermediate evolution was subject to desorption/adsorption equilibrium.